Odpowiedź:
[tex]a)\\ \frac{3}{x - 2} = \frac{4}{2x + 1}\\ \\ 4 (x - 2) = 3 (2x + 1)\\ \\ 4x - 8 = 6x + 3\\ \\ -2x = 11 / : (-2)\\ x = - 5,5[/tex]
[tex]b)\\\frac{2}{3} = \frac{3x+2}{2x - 2} \\\\3 (3x + 2) = 2 (2x - 2)\\\\\9x + 6 = 4x - 4\\\\5x = - 10 / : 5\\x = - 2[/tex]
[tex]c)\\\frac{6x-1 }{x + 1} = \frac{2,3}{1,2} \\\1,2 (6x - 1) = 2,3 (x + 1)\\7,2x - 1,2 = 2,3x + 2,3\\7,2x - 2,3x = 2,3 + 1,2\\4,9x = 3,5 / : 4,9\\x = 35/ 49 = 5/7[/tex]
[tex]d)\\\frac{-x}{3x - 1} = \frac{2x }{1 - 6x} \\\\-x ( 1 - 6x) = 2x ( 3x - 1)\\-x + 6x^{2} = 6x^{2} - 2x\\x = 0[/tex]
Szczegółowe wyjaśnienie: